2023
DOI: 10.3390/jof9030327
|View full text |Cite
|
Sign up to set email alerts
|

Successful Multimodal Therapy with Intracerebral Liposomal Amphotericin B and Systemic High-Dose Isavuconazole in Proven Disseminated Aspergillosis

Abstract: We report the case of a 32-year-old man receiving chemotherapeutics for an acute B-lymphoblastic leukemia who developed proven cerebral and pulmonary aspergillosis with Aspergillus flavus. Because of progressive fungal disease with neurological deterioration despite adequate systemic antifungal therapy and surgical debridement, intracerebral administration of liposomal amphotericin B was initiated at 5 mg twice weekly. This led to improvement of the cerebral infection. Surgical debridement of a pleural Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Cases of disseminated mucormycosis in children with leukemia, treated successfully with ISA and liposomal AmB, have been reported ( 25 , 26 ). Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA ( 27 ). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of disseminated mucormycosis in children with leukemia, treated successfully with ISA and liposomal AmB, have been reported ( 25 , 26 ). Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA ( 27 ). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of disseminated mucormycosis in children with leukemia, treated successfully with ISA and liposomal AmB, have been reported (25,26). Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA (27). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of disseminated mucormycosis in children with leukemia, treated successfully with ISA and liposomal AmB, have been reported (25,26). Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA (27). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA (28,29).…”
Section: Discussionmentioning
confidence: 99%